2021
DOI: 10.1002/adfm.202100954
|View full text |Cite
|
Sign up to set email alerts
|

IR780‐Loaded Hyaluronic Acid@Gossypol–Fe(III)–EGCG Infinite Coordination Polymer Nanoparticles for Highly Efficient Tumor Photothermal/Coordinated Dual Drugs Synergistic Therapy

Abstract: A novel strategy called “two‐stage dual‐synergistic tumor therapy (TDTT),” which combines photothermal therapy with infinite coordination polymers (ICPs) chemotherapy at the first stage in the short term and two drugs of ICPs synergistic chemotherapy (coordinated dual drugs chemotherapy) at the second stage in the long term, is proposed. This strategy is achieved by preparing IR780‐loaded hyaluronic acid (HA) encapsulated gossypol–Fe(III)–epigallocatechin gallate (EGCG) ICP nanoparticles (HA@IRGFE ICP NPs), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 79 publications
3
36
0
Order By: Relevance
“…31 As shown in the Supporting Information, we measured the PCE of T780T to be 38.5% (Figure 2g,h), which is higher than most of the reported heptamethine cyanine PSs (PCE ≈ 3−20%). 8,22,32 To study the photothermal conversion mechanism of T780T, we compared the temperature change of IR780 (10 μM) and T780T (5 μM) at the same power density of 0.3 W cm −2 in DMSO as dispersed states and in H 2 O as aggregated states. As shown in Figures S5 and S6, for the same normalized concentration of IR780, the temperature elevations of T780T (5 μM) in both solvents were larger than those of IR780 (10 μM), indicating that the promising photothermal behavior of T780T was mainly caused by the involvement of the TPE unit.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 As shown in the Supporting Information, we measured the PCE of T780T to be 38.5% (Figure 2g,h), which is higher than most of the reported heptamethine cyanine PSs (PCE ≈ 3−20%). 8,22,32 To study the photothermal conversion mechanism of T780T, we compared the temperature change of IR780 (10 μM) and T780T (5 μM) at the same power density of 0.3 W cm −2 in DMSO as dispersed states and in H 2 O as aggregated states. As shown in Figures S5 and S6, for the same normalized concentration of IR780, the temperature elevations of T780T (5 μM) in both solvents were larger than those of IR780 (10 μM), indicating that the promising photothermal behavior of T780T was mainly caused by the involvement of the TPE unit.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, IR780 could hopefully be retained in cancer cells because it exhibits resistance against the drug efflux transporter ATP-binding cassette (ABC) . However, similar to the other tricarbocyanine dyes, IR780 can be easily photobleached, and the photothermal conversion efficiency (PCE) is not adequately high . Moreover, any improvement in photostability and PCE by structural modifications may affect the tumor targeting properties of the dye, since the structure–activity relationship for tumor targeting is not clear yet .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Benefiting from the inherently temperature-sensitive property of TRPV1, nanomaterials with the ability to convert the absorbed photon energy to heat energy would be ideal nanoagonists for remote-controlled activation of TRPV1 signaling. 15,16 Compared with other targeting moieties, such as folic acid and hyaluronic acid, 17–19 functionalization of nanomaterials with ligands to target TRPV1 channels offers not only the prospect of target recognition but also an effective route to spatiotemporally regulate cancer cellular activity. On the basis of this concept, Han and co-workers have demonstrated that copper sulfide nanoparticles can modulate TRPV1 channels and trigger the ion over-flux in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, more than 20 000 different MSPs have been designed and prepared due to their huge application potential in many fields benefit from advantages on structural design. [2][3][4][5][6][7][8] The studies of these metal centers of MSPs that have received much attention in literature mainly focus on metals ions, such as Cr(III), Fe(III), Al(III), Mg(II), Mn(II), Cd(II), Co(II), Cu(II), Cu(I), Zn(II), and Zr(IV)), and their clusters, for examples, Zn 4 O(COO) 6 , Cu 2 (COO) 4 , Cr 3 O(H 2 O) 3 (COO) 6 , and Zr 6 O 4 (OH) 10 (H 2 O) 6 (COO) 6 ). [9] Amongst these, the studies on vanadium MSPs (V-Supramolecular) are far fewer than those tens of thousands of other metalsbased MSPs, considering the wide range of clusters and complexes that can be formed with vanadium nodes.…”
mentioning
confidence: 99%